Opening gap width influences distal tibial rotation below the osteotomy site following open wedge high tibial osteotomy - Kim, Jun-Ho (PLoS One, 2020)
PURPOSE: Although rotation of the distal portion of the tibia below the osteotomy site is considered an inevitable change in the axial plane in open wedge high tibial osteotomy (HTO), several studies on this issue have shown contradictory results. The purpose of this study was, therefore, to determine the direction and amount of distal tibial rotation following open wedge HTO using a three-dimensional reconstructed model. METHODS: This study involved 41 patients (42 knees) undergoing open wedge HTO for primary medial osteoarthritis. Distal tibial rotation was measured on the overlaid tibial plateau of a preoperative and postoperative 3-dimensional reconstructed model based on computed tomography. RESULTS: The mean distal tibial external rotation was 2.7° ± 2.3° (range, -0.9° to 9.9°), and the opening gap was larger in the group with > 3° distal tibial rotation than in the group with ≤ 3° distal tibial rotation (11.4 mm vs. 9.6 mm, P = 0.027). Multiple regression analysis showed that the opening gap was the only predictor of distal tibial rotation. On receiver operating characteristics analysis, an opening gap of 10 mm was found to be the optimal cutoff value for achieving greater than 3° of distal tibial rotation. CONCLUSIONS: Following medial opening wedge HTO, the distal tibial portion below the osteotomy site rotated approximately 3° externally. The magnitude of the external rotation of the distal tibia was affected by the opening gap width.